Microwave absorption and electromagnetic interference shielding properties of carbon black/MnNiZn ferrite nanocomposites-filled paraffin wax in the frequency range (8.8–12 GHz): Microwave absorption behavior - Houbi, A.; Atassi, Y.; Zharmenov, A.A.; Bagasharova, Zh.T.; Myrzalieva, S.K.; Kadyrakunov, K.B.; Karibayev, B.A. (Recent Contributions to Physics, 2022)
In this present work, we offer the design of good, wideband microwave absorption materials (MAMs) based on CB/Mn0.1Ni0.5Zn0.4Fe2O4 (carbon black/MnNiZn ferrite). The ferrite is prepared by a self-combustion method using sucrose as fuel. The chemical is utilized for the synthesis of carbon black nanopowder is carbon black powder (2–8 μm). Then, the operation is continued via mixing carbon black and MnNiZn ferrite through the grinding balls. Four various weight ratios of CB/Mn0.1Ni0.5Zn0.4Fe2O4 (1:0, 1:1, 2:1, and 3:1) with various thicknesses (2–4–6 mm) are prepared. X-ray diffractometry and FTIR spectroscopy are utilized in order to characterize samples. The morphology of the powders is investigated by SEM. The electromagnetic interference (EMI) shielding and microwave absorption properties are measured in the frequency band of 8.8–12 GHz to accomplish the practical characterization. The MAMs show broad bandwidths under -10 dB in the range of 0.3–3.2 GHz and reasonable surface density in the range of 2.91–3.66 kg/m2 with a weight ratio within a paraffin matrix of 40% w/w. The MAM shows a minimal reflection loss of -18.3 dB at the frequency of 11.4 GHz for the thickness of 2 mm. The maximum shielding efficiency is 18.5 dB at 11.5 GHz for 2 mm thickness of the CB/F-21 nanocomposite sample.